Evaluation of the use of a GPS data-logging device in a snowsport environment - Dickson, T. J.; Terwiel, F. A.; Waddington, G.; Trathen, S. (Procedia Engineering, 2011)
This research explores the usability of a GPS data-logging device designed for team-based sports as a mechanism for collecting data on snowsport participants` temporal and spatial use of alpine resorts. Usability for participants was high, however there are a few issues for the research that were challenging, but the quality and quantity of data obtained outweighs any limitations identified. Thus the researchers believe that GPS Spi Elite is a useful resource for tracking snowsport participants` temporal and spatial use of alpine resorts.